Cholelithiasis and cholecystectomy increase the risk of gastroesophageal reflux disease and Barrett’s esophagus - Huang, Yu; Cai, Yicong; Chen, Yingji; Zhu, Qianjun; Feng, Wei; Jin, Longyu; Ma, Yuchao (Frontiers in Medicine, 2024)
Background: Cholelithiasis or cholecystectomy may contribute to the development of gastroesophageal reflux disease (GERD), Barrett's esophagus (BE), and esophageal adenocarcinoma (EAC) through bile reflux; however, current observational studies yield inconsistent findings. We employed a novel approach combining meta-analysis and Mendelian randomization (MR) analysis to comprehensively assess the association between them. Methods: A search of literature until 3 November 2023 was done in PubMed, Web of Science, and Embase. Meta-analysis of observational studies assessing correlations between cholelithiasis or cholecystectomy and GERD, BE, and EAC risk factors were conducted. MR analysis was then employed to assess the causative impact of genetic pre-disposition for cholelithiasis or cholecystectomy on these esophageal diseases. Results: The results of the Meta-analysis indicated that cholelithiasis was significantly linked to an elevated risk in the incidence of BE (RR, 1.77; 95% CI, 1.37-2.29; P < 0.001) and cholecystectomy was a risk factor of GERD (RR, 1.37; 95%CI, 1.09-1.72; P = 0.008). We observed significant genetic associations between cholelithiasis and both GERD (OR, 1.06; 95% CI, 1.02-1.10; P < 0.001) and BE (OR, 1.21; 95% CI, 1.11-1.32; P < 0.001), as well as a correlation between cholecystectomy and both GERD (OR, 1.04; 95% CI, 1.02-1.06; P < 0.001) and BE (OR, 1.13; 95% CI, 1.06-1.19; P < 0.001). After adjusting for common risk factors, such as smoking, alcohol consumption and BMI in multivariate analysis, these variables still increase the risk of GERD and BE. Conclusions: Our study revealed that both cholelithiasis and cholecystectomy elevate the risk of GERD and BE. However, there is no observed increase in the risk of EAC, despite GERD and BE being the primary pathophysiological pathway leading to EAC. Therefore, it is advisable for patients with cholelithiasis and cholecystectomy to be vigilant regarding esophageal symptoms; however, invasive EAC cytology may not be necessary.